2021
DOI: 10.1111/stul.12177
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Roles or Syntactic Functions: The Effects of Annotation Scheme on the Results of Dependency Measures

Abstract: The annotation scheme of dependency treebanks might have an impact on the results of linguistic analysis, thus leading to different interpretations of linguistic phenomena. This study compares the results of two widely used dependency measures, i.e., dependency direction and dependency distance, based on 18 parallel Universal Dependencies (UD) annotated treebanks and 18 corresponding Surface‐Syntactic Universal Dependencies (SUD) annotated treebanks. The results show that (1) Based on the semantic UD and synta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…However, the syntactic network approach particularly relies on dependency-treebank resources, which require a lot of manual work to ensure parsing accuracy, making it di cult to use frequently to monitor learners' interlanguage development (especially in the Chinese context). Additionally, previous studies have shown that the annotation scheme used can signi cantly affect the results of dependency measures (Yan & Liu, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, the syntactic network approach particularly relies on dependency-treebank resources, which require a lot of manual work to ensure parsing accuracy, making it di cult to use frequently to monitor learners' interlanguage development (especially in the Chinese context). Additionally, previous studies have shown that the annotation scheme used can signi cantly affect the results of dependency measures (Yan & Liu, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…To some extent, the annotation scheme of SUD is a simplified version of Mel'čuk's original system. Moreover, there have already been several studies that make comparisons between the SUD and UD (Osborne and Gerdes 2019, Yan and Liu 2019, 2022). Also, apart from SUD, another approach based on MTT can be found in Mille et al (2012) and in Poiret et al (2021).…”
mentioning
confidence: 99%